REGIONAL CHEMOINFUSION ARTERIA THORACICA INTERNA IN THE COMBINEITED TREATMENT OF THE BREAST CANCER - K. R. Umarova; D. T. Arybzhanov; A. N. Ormanov (Креативная хирургия и онкология, 2017)
Direct results  nonadjuvant intraarterial chemotherapy are analysed at breast cancer  3 stages at  30 patients under  scheme  Taxotere  75mg/m2, Doxorubicini  60mg/m2. At the analysis  of  results  after 2 rates  intraarterial chemotherapy partial  regress  at  19 (63,3%) patients, stabilization of process at 11 (36,7%) patients is noted. After 4х rates intraarterial chemotherapy significant regress  of a tumor  is noted at 15 (50%) patients, partial regress at 12 (40%) patients and  stabilization of process  at 3 (10%)  patients. Thus after 4 rates nonadjuvant intraarterial chemotherapy 27 (90%) patients it is lead radical mastectomy.